Analisis Kelayakan Finansial Usaha Telur Asin Di Desa Tegal Kunir Lor Kecamatan Mauk Kabupaten Tangerang (Studi Kasus Home industry Telur Asin Bapak Rosid) - Heldyana Nawwara Khansa; T. Saiful Bahri; Lukman Hakim (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
Eggs are one of the most commonly consumed foodstuffs. Processed eggs that people like to consume are salted eggs with relatively cheap prices and easy to obtain. With a lot of consumer demand, many salted egg businesses have sprung up. One of them is the salted egg business owned by Mr. Rosid in Tegal Kunir Lor Village, Mauk District, Tangerang Regency. This salted egg business is the main livelihood of Mr. Rosid. The purpose of this study was to analyze the eligibility of Mr. Rosid's salted egg business in Tegal Kunir Lor Village, Mauk District, Tangerang Banten Regency in terms of financial aspects. The results of the study showed that Mr. Rosid's salted egg business in Tegal Kunir Lor Village, Mauk District, Tangerang Regency was eligible to run from a financial aspect with an R/C value of more than 1, NPV has a positive value, B/C value more than 1, IRR is bigger than the interest rate, PP is faster than the economic life of the business Production BEP has a value less than the total production and the price BEP is less than the selling price. Based on the sensitivity analysis of the investment criteria results with the assumption that production costs will increase by 10% with fixed benefits and the assumption of benefits will decrease by 10% with fixed production costs, shows that the salted egg business is still feasible to run or do business even though production costs increase or benefits decrease.